Influenza surveillance and control in the Western Pacific Region - Hitoshi Oshitani (World Health Organization Regional Office for the Western Pacific, 2010)
The Western Pacific Region is considered a source of new antigenic variants of influenza viruses and a potential source for pandemic influenza. Although influenza surveillance in the region has made great progress in recent years, the 2009 pandemic identified issues that need addressing to develop better prevention and control strategies for seasonal and pandemic influenza.